NEGLECTED COXITIS TUBERCULOSA MANAGEMENT IN CHILDREN - Sulis Bayusentono; Erwin Ramawan; Henry Dominica (Journal Orthopaedi and Traumatology Surabaya)
Background: Tuberculosis is one of serious health problems throughout the world, including in Indonesia. The incidence of tuberculosis continue to increase annually, especially the case of bone tuberculosis which is part of tuberculosis extra pulmonary as much as 10-20%.